Rút gọn biểu thức \(M=\tan^2x-\sin^2x\).
\(M=\tan^2x\) | |
\(M=\sin^2x\) | |
\(M=\tan^2x\cdot\sin^2x\) | |
\(M=1\) |
Chọn phương án C.
Dùng máy tính cầm tay:
Vậy \(M=\tan^2x\cdot\sin^2x\).
Chọn phương án C.
\(\begin{aligned}
M&=\tan^2x-\sin^2x\\
&=\dfrac{\sin^2x}{\cos^2x}-\sin^2x\\
&=\dfrac{\sin^2x-\sin^2x\cdot\cos^2x}{\cos^2x}\\
&=\dfrac{\sin^2x\left(1-\cos^2x\right)}{\cos^2x}\\
&=\dfrac{\sin^2x\cdot\sin^2x}{\cos^2x}\\
&=\dfrac{\sin^2x}{\cos^2x}\cdot\sin^2x\\
&=\tan^2x\cdot\sin^2x.
\end{aligned}\)